Upaya Kepolisian Dalam Penegakan Hukum Terhadap Tindak Pidana Perdagangan Wanita Dan Anak Di Kota Samarinda Provinsi Kalimantan Timur - Haris Retno Sumiyati; Emilda Kuspraningrum (Jurnal Risalah Hukum, 2007)
According to Asean Development Bank (ADB) report that for about one to two million people had been sold. Most of them are from poor country, 150.000 from West Asia country and 225.000 from North West Asia Country. The main problem in reducing trafficking in women and child is the weaknesses of law enforcement. Solvement of this case is an ice mount fenomena where the tripe case which accord is more than success to solve and brought to the law process by assosieted party. Key words : penegakan hukum (law enforcement), tindak pidana (criminal), perdagangan wanita dan anak (trafficking in women and children), kepolisian (police department).